Le crayon bleu de la censure : oeuvres d’auteurs français interdites au Portugal entre 1933 et 1974 - Gonçalves, Luís Carlos Pimenta (2018)
The Censor’s Blue Pen: Works by French Authors Banned in Portugal between 1933 and 1974. The dictatorial regime imposed by the Estado Novo regime in force in Portugal between 1933 and 1974 imposed a severe censorship of publications in general and more specifically to books published in Portugal and abroad. Because of the influence that French culture had, many authors, ancient and contemporary, from Flaubert to Sartre going through Sagan, had their works banned. The reasons for the ban were several: the persecution of the author, the work and sometimes to the editor, as exemplified by Francisco Lyon de Castro and his Europa-América publishing company. Besides the memories of those who directly suffered from censorship, writers, publishers and booksellers, there are other evidences in these legal proceedings instructed by the Black Book about the Fascist regime that published in 1981 Books banned by the fascist regime, censorship circulars and arrest proceedings. The extensive list includes French works in the original language or translated such as Madame Bovary, Bonjour Tristesse or Bel Ami, which will be discussed in more detail in this article, analyzing the circumstances of its prohibitions. If the censorship of the press was systematic and permanent, the book’s was erratic and circumstantial, largely for lack of means and resources as indicated by Álvaro Salvação Barreto, General Director of censorship between 1932 and 1944. Thus, sometimes apparently inexplicably, the same work could be banned and some time later this ban could be lifted, as with Mademoiselle Fifi of Maupassant.